Structural and electrical properties of anodic aluminum oxide-template assisted InSb nanowires via electrochemical deposition - Fayyadh, Osamah Ali (2019)
The indium antimonide (InSb) material is a remarkable combination of group III-V due to it is narrow band gap and high electron mobility. InSb has been widely employed in various optoelectronic and electronic devices such as in medical application, biosensor, infrared detectors, and emitters. This can be realized by investigating the conductive layer conditions to achieve nanowires with uniform diameter and length as well as structurally controlled nanowires where ratio can be optimized. This thesis aims to study the AAO template conditions on morphology, structural and electrical properties of InSb nanowires via template-assisted electrochemical deposition technique. Various strategies used to produce morphologically controlled nanowires with desired properties includes effects of conductive layer thicknesses of 11 nm, 65 nm, 130 nm and 260 nm. The AAO templates were then covered with insulating tape at the bottom of the conductive gold layer, to study the effects of In and Sb ions direction to the nanowires growth. The morphology images indicate that the AAO template covered with insulating tape have less overgrowth rough film and smoother sidewall of the nanowire. Meanwhile, the long nanowires with length about 6 μm and rough sidewall were observed from uncovered AAO template, which is due to the overgrown rough film that attached to the sidewall of the nanowires. The overall EDX analysis shows that the sample with insulating tape exhibited better morphology and stoichiometric ratio. It was found that the XRD results exhibited the high crystallinity and polycrystalline characteristics in the nanowires. Moreover, the highest conductivity was achieved among the covered and uncovered samples at 12 minutes with insulating tape sample (7.96 x 10-4 Ω-1cm- 1). In conclusion, the achievement of all these parameters will allow the InSb nanowires to be designed and generated for future nanowires device applications such as biosensor and photovoltaic.